Evaluasi Mekanisme Pengelolaan Retribusi Izin Usaha Perikanan sebagai Upaya Peningkatan Pendapatan Asli Daerah Kabupaten Bengkalis - Fiska Riana Sari; Husni Mubarak (Politeknik Negeri Bengkalis, 2021)
This study aims to determine the acceptance, management, efectiviness and factors that affect the fisheriesbusiness permit retribution as an effort to increase locally-generated revenue in Bengkalis regency. The results of this research is that the mechanism for managing levies for fisheries business permits in Bengkalis Regency is constrained by the legality process or permits processing which takes a long time, because there are several requirements that must be met and sent to different agencies, ineffective while in 2020 it was categoriez as very effective with an achievement of 100,21% with the realization reaching Rp. 288.000.00,-. The problem is the low receipt of retribution for fisheries business permits, namely aquaculture business land which is peat land and/or primary natura forest and includes HPT, the amount of cost that must be incurred to obtain a business license, the lack of understanding of shrimp farming business actors towards regulations management of SIUP, business actors do not understand the PIPPIB process for primary natural forests and peatlands, and there is no legal action against business actors who do not have SIUP.